Teaching and Learning Styles as Predictors of Students’ Achievement in English Language in some Selected Secondary Schools - Opeyemi Olajumoke OLOFINSAWO; Francis Ogbonnaya EZEOKOLI; Isaac Adebayo ADEROJU; Oluwatosin Hossanah ADENIYI (Program Doktor Pendidikan FKIP Universitas Lampung, 2026)
The English language plays a leading role in academic success and advancement of students in Nigeria. Students’ low competence in English has led to unacceptable rate of failure in it and other content area subjects, especially at the secondary school level. Research in English language teaching has to a large extent, sought to enhance effective teaching and learners’ performance and communicative skills. Literature reveals a preponderance of studies in English language teaching and learning in relation to attitudes, interests, gender, approaches, methods, strategies and use of technology. However, teaching and learning styles as essential elements of the teaching-learning process have drawn the attention of few researchers and stakeholders. This study therefore, examined teaching and learning styles of teachers and students as predictors of students’ achievement in English. Correlational research design was adopted. Purposive and simple random sampling techniques were used to select 115 teachers and 446 students for this study. Instruments used were: Teaching Style Questionnaire (r=87), Learning Style questionnaire (r=0.77) and Achievement test in English Language (r=0.67). Results indicate that students most preferred learning styles are: kinesthetic (44.8%) and visual learning styles (28.7%) while teachers most preferred teaching styles include: Demonstrator (43%), facilitator (19%) and delegator (17%). Furthermore, there was a significant positive but weak relationship between learning style and achievement in English (r= 0.168). Additionally, learning style has a positive significant contribution to students’ achievement (B= 0.351,t=2.616; p<.05). This study therefore, recommend that teachers should be match teaching styles with learning styles and and should use teaching styles that are students centered.